Answer:
x = -1
Explanation:
Rewrite the equation as 6x + 8 = 2
Subtract 8 from both sides of the equation.
6x = 2 − 8
Subtract 8 from 2.
6x = −6
Divide each term in 6x = −6 by 6 and simplify.
Divide each term in 6x = −6 by 6.
![(6x)/(6) = (-6)/(6)](https://img.qammunity.org/2023/formulas/mathematics/college/501n2o3h0so0l00km50mheoqwp3fpvxd44.png)
Simplify the left side.
![x=(-6)/(6)](https://img.qammunity.org/2023/formulas/mathematics/college/mwl88ir8fvgqe7ulhw1ax55833bunr2ajm.png)
Simplify the right side.
Divide -6 by 6
x = -1